2004
DOI: 10.1038/sj.sc.3101584
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical therapy options for neurogenic detrusor overactivity

Abstract: Objectives: This review considers intravesical treatment options of neurogenic detrusor overactivity and discusses the underlying mechanism of action, clinical safety and efficacy, and the future trends. Methods: The available literature was reviewed using medline services. Results: Oral anticholinergic drugs are widely used to treat detrusor overactivity, but they are ineffective in some patients or cause systemic side effects such as blurred vision or dry mouth. As an alternative, topical therapy strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 66 publications
0
23
0
4
Order By: Relevance
“…7 We believe that intermittent catheterisation with oral or intravesical 8 pharmacotherapy to control detrusor hyperreflexia and detrusor-sphincter dyssynergia 9 is the first choice of bladder drainage for these patients. When our patient started taking modified release formulations of oxybutynin and alfuzosin, symptoms of autonomic dysreflexia subsided.…”
Section: Discussionmentioning
confidence: 99%
“…7 We believe that intermittent catheterisation with oral or intravesical 8 pharmacotherapy to control detrusor hyperreflexia and detrusor-sphincter dyssynergia 9 is the first choice of bladder drainage for these patients. When our patient started taking modified release formulations of oxybutynin and alfuzosin, symptoms of autonomic dysreflexia subsided.…”
Section: Discussionmentioning
confidence: 99%
“…Counter-intuitively, the serum levels of oxybutynin after intravesical administration are as high as when taken orally. [1] However, since first-pass liver metabolism is circumvented with this approach, a reduced side-effect profile is observed. Sideeffects are predominantly thought to be mediated by the metabolite N-desethyl oxybutynin.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Continence was restored in all 17 children investigated. [1] A further study demonstrated a reduced requirement for oral medication and improved quality of life for children treated with botulinum toxin type A. [11] Urodynamic efficacy lasts for about 6 months, after which repeated injections are necessary.…”
Section: Pharmacotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 However, some patients cannot be controlled by oral medications, despite maximal dosages, and some cannot tolerate the side effects, 5,6 such as a dry mouth, visual disturbance or constipation, at any dosage. Recently, to minimize the side effects of anticholinergics, intravesical instillations, such as oxybutynin 7,8 or vanilloids, 9 have been tried. Of these, vanilloids, unmyelinated C-fiber blockers (capsaicin or resiniferatoxin), have been tried, but the effects of the treatment are equivocal.…”
Section: Introductionmentioning
confidence: 99%